THU0152 Who are the patients with rheumatoid arthritis (RA) who are getting comorbidity screening procedures in accordance with guidelines? a study of 769 established ra patients. (15th June 2017) - Gossec, L; Foissac, F; Soubrier, M; Fayet, F; Bardin, T; Beauvais, C; Chales, G; Chary-Valckenaere, I; Dernis, E; Euller-Ziegler, L; Flipo, R-M; Gaudin, P; et al.
Abstract : Background: Patients with RA are either more at risk of, or less well screened for, several comorbidities including cardiovascular (CV) risk, cancer, infections and osteoporosis.[1] Recommendations have been developed on how and at what frequency to screen for comorbidities in RA patients.[2] Objectives: to characterise patients who are being screened correctly (i.e., in accordance with recommendations). Methods: Study design: This was an open long-term (3 years) extension of the COMEDRA 6 month randomized controlled trial in which patients with definite, stable RA were visiting a nurse for comorbidity assessment and screening counselling.[3] For this analysis, only the final visit data were used cross-sectionally. Assessment of comorbidity screening: A score was developed to quantify comorbidity screening procedures in accordance with guidelines:[4] this score gives 50 points to CV risk screening, 20 points to cancer screening, 20 points to pneumococcus and influenza vaccination and 10 points to osteoporosis screening. The score ranges 0–100 and 0 indicates optimal screening. Factors associated with optimal screening: demographic and disease characteristics were compared between patients considered well-screened (lowest tertile for screening score) versus other patients. Statistical analysis: Variables with p<0.20 in univariate analysis were entered into the multivariate analysis using a backward stepwise logistic regression. Results: 769 patients were assessed: mean (±SD) age 62 (±11) years, mean disease duration 17 (±10) years; 614 (80%) were women and 535 (70%) were receiving a biologic. Disease was well-controlled (mean DAS28 2.8±1.3). The mean comorbidity screening score was 24.3 (±17.8) (range, 0–100). The 316 patients (41% of all patients) in the lowest tertile for this score (i.e., with a score ≤15) were less often smokers: odds ratio [95% confidence interval] 0.45 [0.28 – 0.72], were more often treated for hyperlipidemia (2.58 [1.85 – 3.61]), and were more often treated with a biologic (1.97 [1.4 – 2.76]). Conclusions: Comorbidity screening is suboptimal in RA. Patients who were better screened were more frequently already followed-up for hyperlipidemia and were more frequently receiving biologics but more less frequently smokers. Thus it seems getting optimal screening may reflect both patient characteristics but also physician attention to comorbidity in certain situations. Empowering patients to be responsible for the comorbidity screening reminders should be explored. References: Ref 1. Baillet A, Gossec L et al. Ann Rheum Dis. 2016;75(6):965–73. Ref 2. Gossec L et al. Joint Bone Spine. 2016;83(5):501–9. Ref 3. Dougados M, Soubrier M et al. Ann Rheum Dis. 2015;74(9):1725–33. Ref 4. Gossec L et al. Arthritis Rheumatol. 2016; 68 (suppl 10): abstract. http://acrabstracts.org/abstract/screening-for-and-management-of-comorbidities-after-a-nurse-led-program-results-of-a-3-year-longitudinal-study-in-776-established-ra-patients/. Acknowledgements: grant from Roche France and from the French National Research Program (PHRC AOM 12072). Disclosure of Interest: None declared